Design and implementation of an android based tomato irrigation system - Machengete, Blessed (Midlands State University, 2017)
The advent of technology has made life easier, smooth and smarter. Smart phones are being applied in all aspects of life, be it Medical field, Military, Aviation or Agriculture. Agriculture is one of the key drivers of Zimbabwe`s Economy. The majority of Zimbabweans venture into farming for both personal sustenance as well as sustenance of the nation as a whole. Small farming projects are being carried out in the backyards of urban areas. People have resorted to growing Potatoes, Beans, Peas, Carrots, Tomatoes, cabbages and many other vegetables for personal consumption as well as for commercial purposes. Most of these people do this on a part time basis. This project seeks to devise a simple low cost android based tomato irrigation system. The user will be able to control the Irrigation system using an android application on a smart phone. This project is developed by using Arduino Uno, SIM900 GSM module, LCD display, soil moisture sensors and water tank level sensor. The android application makes use of the GSM technology to send commands to the irrigation system. GSM network is widespread in Zimbabwe and have almost reached every corner of the country. This makes the Android application reliable and cheap to use.